Impact of Agricultural Commercialization on Household Food Insecurity in Kenya - Kipkorir , Peter; Ngeno , Vincent; Chumo , Chepchumba (African Journal of Education,Science and Technology (AJEST), 2023)
Agricultural production in Kenya has remained low with relative food insecurity affecting many citizens in most parts of the country because of the increase in population growth over the past two decades. This study, specifically, examined the impact of agricultural commercialization on household food insecurity in Kenya using Panel data from Kenya’s 2020 Covid-19 Rapid Response Phone Survey. An endogenous switching regression was utilized to establish the impact of agricultural commercialization on household food security and at the same time account for endogeneity and self-selection problems. The endogenous switching regression (ESR) model also controlled for structural differences between the commercialized and the non-commercialized households in terms of food security outcome functions. Particularly, land size had a significant positive impact on the food security of the commercialized households while it had a negative but significant impact on the food security of the non-commercialized households. Therefore, households with large land sizes are more likely to improve by a greater extent household food security compared to households with small land sizes when they participate more in the market. However, age,women empowerment and internet access recorded a significant homogenous effect on the food security of the households among the commercialized and non-commercialized group of households. The results further suggest that both the observed and unobserved characteristics influence the decision to commercialize and food security outcome give the decision to commercialize. The results reveal that households participating in agricultural commercialization would experience improved food security through increased dietary diversity. The study recommends that there is a need to support agricultural commercialization to increase household food security. This could be achieved by empowering households through adequate online training and education on agricultural commercialization, improving infrastructures and institutions such as internet connectivity, credit and commercial institutions.